Structural Characterization of Paraffin Wax Soot and Carbon Black by XRD - N. Mohan1, Anu; Manoj1, B.; John1, Jerin; Ramya1, A.V. (Asian Journal of Chemistry, 2013)
From past few decades, an exponential increase in the research related to carbon nanomaterials and their excellent applications has been witnessed. Realizing the need for new potential precursors and cost effective production methods, we have investigated two precursors-paraffin wax soot (CS) and carbon black (CB). Structural and morphological features of the samples are analyzed by various techniques such as X-ray diffraction, high resolution scanning electron microscopy and electron dispersive spectroscopy. The lateral size of the aromatic lamellae, stacking height, the average spacing of the (002) crystallographic planes (d002) and aromaticity are found to be 15.12 Å, 44.30Å, 3.57 Å, 0.912 and 15.26 Å, 43.23 Å, 3.68 Å, 0.986 respectively for paraffin wax soot and carbon black. Very low g and p band intensity ratio shows a low amount of disorder in the samples. SEM micrographs of the samples reveal non-uniform carbon nanospheres of particle sizes 26-94 nm.